2019
DOI: 10.1186/s40249-019-0549-1
|View full text |Cite|
|
Sign up to set email alerts
|

How Thailand eliminated lymphatic filariasis as a public health problem

Abstract: Background Lymphatic filariasis is endemic in nine of the eleven Member States of the World Health Organization South East Asia Region. This article describes the intensive interventions with the National Programme for Elimination of Lymphatic Filariasis in Thailand since its launch in 2001 till the validation of its elimination in 2017. Methods A baseline epidemiological survey was initiated in 2001 to identify both brugian and bancroftian filarial areas and delineate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…It demonstrated through its evaluation surveys-the Stop-MDA surveys and Transmission Assessment Surveys (TAS)-below transmission threshold rates that enabled its validation of LF elimination. 3 A recent study in India proved that participation in MDA programs was a behavioral factor that can affect the occurrence of filariasis (OR = 1.8 and OR = 13.75). 4 In Indonesia, after the fifth year of the MDA program in Pekalongan City, the area is no longer included in the filariasis-endemic areas and the transmission parameters have no potential in causing the spread of filariasis.…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrated through its evaluation surveys-the Stop-MDA surveys and Transmission Assessment Surveys (TAS)-below transmission threshold rates that enabled its validation of LF elimination. 3 A recent study in India proved that participation in MDA programs was a behavioral factor that can affect the occurrence of filariasis (OR = 1.8 and OR = 13.75). 4 In Indonesia, after the fifth year of the MDA program in Pekalongan City, the area is no longer included in the filariasis-endemic areas and the transmission parameters have no potential in causing the spread of filariasis.…”
Section: Introductionmentioning
confidence: 99%
“…Several species of Mansonia have been reported as vectors in Kalimantan, namely, M. bonneau (Diptera: Culicidae) as the primary vector for filariasis caused by non-periodic B. malayi in the indigenous Dayak areas of East Kalimantan [ 29 ] and M. uniformis as the swamp-type filariasis vector in Batala District, South Kalimantan . M. uniformis , M. dives , and M. bonneau are the primary vectors of subperiodic B. malayi transmission [ 30 ] and are periodically nocturnal in some areas of South Thailand and Nakhon Si Thammarat, Narathiwat Surat Thani, Pattani, Phattalung, and Yala Province, and the secondary vectors are M. dives , Mansonia annulata , and Mansonia annulifera [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the history of LF in Thailand, an old study reported that among 4112 persons examined in many villages, 863 were positive for microfilariae, of whom 215 showed filarial disease (Iyengar 1953). Currently, most cases of LF are reported in immigrants (Nithikathkul et al 2006;Rojanapanus et al 2019). Many immigrants reside in Thailand, so many studies have focused on this population group.…”
Section: Thailandmentioning
confidence: 99%